2015
DOI: 10.18632/oncotarget.4773
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput simultaneous screen and counterscreen identifies homoharringtonine as synthetic lethal with von Hippel-Lindau loss in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) accounts for 85% of primary renal neoplasms, and is rarely curable when metastatic. Approximately 70% of RCCs are clear-cell type (ccRCC), and in >80% the von Hippel-Lindau (VHL) gene is mutated or silenced. We developed a novel, high-content, screening strategy for the identification of small molecules that are synthetic lethal with genes mutated in cancer. In this strategy, the screen and counterscreen are conducted simultaneously by differentially labeling mutant and reconstituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The principles of synthetic lethality allow us to treat a tumor with minimal toxicity to non-cancerous cells by exploiting vulnerabilities caused by oncogenic alterations. [ 20 23 ] Indeed, this approach has previously been utilized to discover synthetic lethal interactions in KRAS -mutant cells. [ 24 ] We devised an approach to identify compounds and experimental drugs that are synthetic lethal with increased RAS signaling caused by loss of the RAS-GTPase activating protein (RAS-GAP) NF1.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of synthetic lethality allow us to treat a tumor with minimal toxicity to non-cancerous cells by exploiting vulnerabilities caused by oncogenic alterations. [ 20 23 ] Indeed, this approach has previously been utilized to discover synthetic lethal interactions in KRAS -mutant cells. [ 24 ] We devised an approach to identify compounds and experimental drugs that are synthetic lethal with increased RAS signaling caused by loss of the RAS-GTPase activating protein (RAS-GAP) NF1.…”
Section: Introductionmentioning
confidence: 99%
“…This VHL protein encoded by the VHL gene is well known as an E3 ubiquitin [8]. It is widely accepted that the a-subunit of hypoxia-inducible factor(HIF-a) is the degradation target of VHL-containing E3 ligase in normal physiological conditions [13,14]. Moreover, the ligand stromal cell-derived factor (SDF)-1 and CXC chemokine receptor 4 (CXCR4) were also regarded as HIF targets, which suggests that HIF activation could lead to the potential metastasis of cancer cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a focused shRNA library screening identified that CDK6, MET, or MEK1 shRNAs may be selectively toxic to VHL-deficient ccRCC cells, but the effect is mediated in an HIF-independent fashion [ 110 ]. In addition, a highly sensitive high-throughput imaging-based platform with 12,800 small molecules identified homoharringtonine (HHT), an FDA-approved drug that may be used to treat chronic myeloid leukemia (CML), as a synthetic lethality partner in VHL-loss tumors [ 111 ]. However, it remains to be determined as to whether HHT affects HIF signaling in this setting.…”
Section: Targeting Vhl Signaling In Ccrccmentioning
confidence: 99%